Design of Wideband Dual-band Substrate Integrated Waveguide Slot Antenna - W. Chen; J. Yu; Z. Yang; X. Yang (Radioengineering)
A dual-band Half Mode Substrate Integrated Waveguide (HMSIW) slot antenna operating at 3.5 GHz and 4.9 GHz is proposed. The two operational bands of the proposed antenna are achieved by combining two HMSIW slot antennas. The -10 dB impedance bandwidth and realized gain of the antenna at 3.5 GHz and 4.9 GHz are 3.47-3.68 GHz with a gain of 3.9 dBi and 4.62-5.16 GHz with a gain of 5.5 dBi, respectively. Compared with the traditional SIW dual-band antenna, the bandwidth of the antenna has been significantly improved. The proposed antenna has a simple structure and exhibits excellent radiation performance in both operating frequency bands, making it suitable for 5G mobile communication systems.